GAMBARAN PENYIMPANAN OBAT DI INSTALSI FARMASI RUMAH SAKIT ISLAM IBNU SINA PADANG PANJANG TAHUN 2022 - NADYA TRILAKSHA; ERPIDAWATI ERPIDAWATI; YASHERLY BACHRI (LP2MTBM MAKARIOZ, 2023)
Storage of drugs in the Pharmacy Installation at the Islamic Hospital of Ibnu Sina Padang Panjang in the arrangement of drugs that are still not neatly arranged on the shelves/drug storage cabinets, which results in difficulties for officers to take drugs in the pharmacy installation warehouse. The purpose of this study is to describe the procedure for storing drugs at the pharmacy installation of RSI Ibnu Sina Padang Panjang This research uses descriptive research method with a qualitative approach. The research informants were 5 people. The data collection method used was based on observation, interviews and documentation guidelines. Data analysis was carried out in an integrative way. The results of this study indicate that the storage space layout has met the requirements. The storage facilities and infrastructure do not meet the requirements and the drug storage system does not meet the requirements for drug storage. The conclusion of this study is that RSI Ibnu Sina Padang Panjang has not been maximized in the application of drug storage, and must improve again in the facilities and infrastructure as well as the drug storage system to meet the requirements.